Intraperitoneal migrating mesh plug wrongfully taken for right colon cancer: A case report. (July 2021) - Haddad, A.; Yahia, D. Bel Haj; Chaker, Y.; Maghrebi, H.; Daghfous, A.; Kacem, M.J.
Abstract: Background: The use of mesh has become nowadays a standard for hernia repairs. It allows a tension-free hernioplasty and has shown that it is an effective way to prevent recurrences. But complications have been described. Intraperitoneal migration of mesh plug is an uncommon complication. Case report: In this paper we report a case of a 57 year old male who has been operated on 12 years ago, he had a mesh plug repair for a ventral incisional hernia. The mesh migrated into the abdominal cavity and it was wrongfully taken for a locally advanced right colon cancer. Colonoscopy was done and biopsies were taken, but the results were not conclusive. He was operated on. We found the mesh that had migrated and eroded the hepatic flexure. There was a granulation tissue that also included some of the small intestine. There was also an abscess in the abdominal wall. He had an en-bloc resection of a part of the abdominal wall, small intestine and right colon. Conclusion: Mesh hernioplasty is a frequent, simple and effective procedure with a low recurrence rate but it can be associated to serious complications such as mesh migration. Highlights: The use of mesh has been a major landmark in surgical techniques reducing the rate of recurrence significantly. Intraperitoneal migration of mesh is an uncommon and a serious complication in hernia repair. It's symptoms are not specific and therefore establishing the right diagnosis is not always possible Surgery is necessary confirm the diagnosis and treat the patient. The resection depends on the organ affected and it can be extensive